KONDISI SOSIAL EKONOMI KELUARGA PENDERES KARET DI KECAMATAN TAMIANG HULU KABUPATEN ACEH TAMIANG (Suatu Studi di Desa Bandar Baru Kecamatan Tamiang Hulu Kabupaten Aceh Tamiang) - Raihani - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2011)
The study entitled "Socio-Economic Conditions in the Village Family Penderes Rubber New Bandar Aceh District Tamiang Hulu Tamiang" aims to Know The Rubber Penderes Socioeconomic Conditions in the village of Bandar Baru. Types of research used in this research is descriptive method with qualitative approach. The population in this study is all the rubber in the village of Bandar penderes New 275 heads of households and sample as many as 27 heads of families taken by random sampling. Data collection techniques used library research and field research with the techniques of data collection by way of observation, documentation and questionnaires. Furthermore, the techniques of data analysis using the percentage formula P = x100%.The results showed that the socio-economic conditions in the village of rubber penderes New Bandar Aceh District Tamiang Tamiang Hulu is still modest compared with other communities in general. while the large rubber penderes income earned each month by an average of Rp 2,444,444.00 and they have been insufficient to meet their needs every day. Furthermore the problems faced in conducting its activities penderes rubber is the rainy season which affects the production of rubber latex per day. Thus, it was indicated that the rubber penderes family or the village of New Airport District Tamiang Hulu regency of Aceh Tamiang have socio-economic conditions are considered. This is consistent with the theory put forward by Suyitno (2005:19): "Indications of a society that has a low socio-economic conditions over more revenue in terms of society itself". Key words: the condition, social and economic